The place of ‘vicarious memories’ in contemporary South Africa - Pillay, K.S. (South African Journal of Higher Education, 2019)
This article examines the role of apartheid memories within a contemporary dispensation. It argues that memories are an important constituent of a democracy which aspires towards social cohesion and social justice ideals. It examines how a group of post graduate students at a selected university make sense of remembering past atrocities, as vicarious witnesses. What emerges is a set of competitive responses to remembering the past. This implies that we have to work much harder at engaging with memories of the past in democratic spaces such as universities, as a way of working towards a fully inclusive national identity.